A comparison of wound healing activity following treatment with three types of Yemen's honey on excision wounds in rats: an animal model (Mustansiria Dental Journal, 2018)
Four groups of adult Wistar Kyoto rats each consist of 6 animals. The rats were experimentally wounded in the posterior neck area. Wounds of Group 1 rats were kept without treatment throughout the experiment. Wounds of Group 2, 3 and 4 were topically applied with fresh unprocessed Yemen's honey Al-Dawa'ani, Al-Jardani and Al-Jawahi, respectively. The rates of wound healing were assessed in all animals. Wounds treated with honey Al-Dawa'ani, Al-Jardani and Al-Jawahi, significantly healed earlier and much faster as compared to wound s of Group 1 animals. Wounds of Group 4 animals treated with honey Al-Jawa/H, significantly accelerate wound healing compared to wound treated with honey Al-Dawa'ani or Al-Jardani There were no significant differences between honey Al-Dawa'ani And honey 2 Al-Jardani in the term of duration of wound healing. Histologically, dermal wounds treated with honey Al-Dawa'ani, Al-Jardani and Al-Jawahi, were rapidly replaced by granulation tissue and advancing epithelialization compared to wound of Group 1 rats. These results indicated the beneficial effects of honey Al-Jawahi for the acceleration of wound healing process in rats.